Risk factors for mortality in patients with acute kidney injury and hypotension treated with continuous veno-venous hemodiafiltration - In Myung Oh; Jang Han Lee; Kyoung Hwa Yoo; Ji Eun Park; Dong Hyun Oh; Mi Jung Kim; Seung Hea Ha; Gi Jong Lee; Jung Hee Kim; Yoon Chul Jung (The Korean Society of Nephrology, 2012)
Background: Continuous veno-venous hemodiafiltration (CVVHDF) is a preferred treatment modality in hemodynamically unstable acute kidney injury (AKI) patients, because it has advantages over intermittent dialysis in terms of hemodynamic stability. However, this patient group still shows a significantly high mortality rate. To aid in the management of these high-risk patients, we evaluated the risk factors for mortality in CVVHDF-treated hypotensive AKI patients. Methods: We studied 67 patients with AKI and hypotension who were treated with CVVHDF from February 2008 to August 2010. We reviewed patient characteristics and laboratory parameters to evaluate the risk factors for 90-day mortality. Results: Of the 67 enrolled patients (male:female=42:25; mean age=69±14 years), 18 (27%) survived until 90 days after the initiation of CVVHDF. There was no significant difference in survival rates according to the etiology of AKI [hypovolemic shock 2/10 (20%), cardiogenic shock 4/20 (20%), septic shock 12/37 (32%)]. Univariate analysis did show significant differences between survivors and non-survivors in the frequency of ventilator use (44% vs. 76%, respectively; P=0.02), APACHE II score (29±7 vs. 34±7, respectively; P=0.01), SOFA score (11±4 vs. 13±4, respectively; P=0.03), blood pH (7.3±0.1 vs. 7.2±0.1, respectively; P=0.03), and rate of urine output <500 mL for 12 hours (50% vs. 80%, respectively; P=0.03). A multivariate Cox proportional hazards model showed that a urine output<500 mL for 12 hours was the only significant risk factor for 90-day mortality following CVVHDF treatment (odds ratio=2.1, confidence interval=1.01-4.4, P=0.048). Conclusion: A urine output<500 mL for 12 hours before the initiation of CVVHDF is an independent risk factor for 90-day mortality in hypotensive AKI patients treated with CVVHDF.